Government and Community Conflict Resolution in Gold Mining Areas without Permission of Bungo District, Jambi Province - Rupaiedah, Ane; Kismartini, Kismartini (Program Pascasarjana Universitas Negeri Makassar, 2020)
Unlicensed Gold Mining in Bungo District caused prolonged conflict between the government and the community. This research is intended to analyze and describe the conflict resolution between the government and the community in the Unlicensed Gold Mining Area in Bungo District. In conducting research the Galtung Conflict Resolution theory is used with qualitative descriptive methods and Milles and Huberman data analysis techniques. The results showed that the process of resolving conflicts of gold mining without permission between the government and the community in Bungo District was carried out in several stages, namely: 1. Peacekeeping at this stage did not provide a deterrent effect for illegal gold miners, this is because during a joint operation of the TNI-POLRI and SatPOLPP occurred , gold miners have already escaped, 2. Peacemaking at this stage the Regional Government has coordinated with Rio or the village head together with the community to find solutions to the PETI problem. The solution offered by the community is the determination of a people's mining area (WPR), 3. Peacebuilding Bungo regency Regional Government through an integrated team to supervise the implementation of the PETI problem in its implementation is still constrained by social factors where the existence of changes in livelihoods that occur from generation to generation demanded on economic needs, and political factors in which there is a pattern of relations between law enforcement officials and cukong or people who facilitate gold mining without permission. To respond to the PETI problem in Bungo Regency: 1). The Bungo District Government needs to crack down on gold miners without permission, 2). Outreach will take place on the impacts of gold mining without permission, 3). Need to make a Regional Regulation (PERDA) in the management of community mining.